Protein quality control and aggregation in the endoplasmic reticulum: From basic to bedside - Chen, Guofang; Wei, Tingyi; Ju, Furong; Li, Haisen (Frontiers in Cell and Developmental Biology, 2023)
Endoplasmic reticulum (ER) is the largest membrane-bound compartment in all cells and functions as a key regulator in protein biosynthesis, lipid metabolism, and calcium balance. Mammalian ER has evolved with an orchestrated protein quality control system to handle defective proteins and ensure ER homeostasis. Nevertheless, the accumulation and aggregation of misfolded proteins in the ER may occur during pathological conditions. The inability of ER quality control system to clear faulty proteins and aggregates from the ER results in the development of many human disorders. The efforts to comprehensively understand ER quality control network and protein aggregation will benefit the diagnostics and therapeutics of ER storage diseases. Herein, we overview recent advances in mammalian ER protein quality control system, describe protein phase transition model, and summarize the approaches to monitor protein aggregation. Moreover, we discuss the therapeutic applications of enhancing ER protein quality control pathways in ER storage diseases.